Role of Workplace Spirituality in Employee Loyalty among Indonesian Millennial Employees - Pratiwi Wijayanti; Martina Dwi Mustika (Faculty of Psychology, Universitas Medan Area, 2021)
This is a novel study that examines the theoretical concept of workplace spirituality and employee loyalty, particularly in the context of millennial employees in Indonesia who currently dominate the local workforce and are thought to have high turnover intentions. This research aims to determine the correlation between each dimension of workplace spirituality and each dimension employee loyalty among millennials in Indonesia. The final participants in the study were 288 millennial employees from 412 initial respondents that fill online questionnaire from 46 cities in Indonesia. All respondents were full-time employees from public and private organizations with minimum two years of work experience. This study first creating the measurement model and then performing structural equation modeling (SEM) to process and interpret the data. The results indicate that each dimensions of workplace spirituality have different effects on the loyalty of millennial employees in Indonesia, which alignment with organizational values is the main reason for staying in the organization.